2016
DOI: 10.1111/ped.12855
|View full text |Cite
|
Sign up to set email alerts
|

Effect of insulin‐like growth factor‐I during the early postnatal period in intrauterine growth‐restricted rats

Abstract: No benefits on body and brain weight gain but an effective increase in hepatic IGFBP-3 was observed after treatment with 2 mg/kg rhIGF-I during the early postnatal period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
(71 reference statements)
0
4
0
Order By: Relevance
“…Three well-defined rat models of IUGR show impaired pancreatic islet development, establish lasting effects in adults, and have been subjected to experimental perinatal interventions to better define the mechanisms leading to diminished islet development and function. Uterine artery ligation (UAL) at embryonic day (E) 18–19 causes an acute decrease in fetal nutrients and oxygen near term (E22), and results in a 10 to 20% reduction in body weight (Delghingaro-Augusto, et al 2014; Ikeda, et al 2016; Ogata, et al 1986; Siebel, et al 2010; Wigglesworth 1964). Maternal dietary restrictions also are widely utilized in rodents to induced IUGR.…”
Section: Animal Models Of Iugr With β-Cell Dysfunctionmentioning
confidence: 99%
“…Three well-defined rat models of IUGR show impaired pancreatic islet development, establish lasting effects in adults, and have been subjected to experimental perinatal interventions to better define the mechanisms leading to diminished islet development and function. Uterine artery ligation (UAL) at embryonic day (E) 18–19 causes an acute decrease in fetal nutrients and oxygen near term (E22), and results in a 10 to 20% reduction in body weight (Delghingaro-Augusto, et al 2014; Ikeda, et al 2016; Ogata, et al 1986; Siebel, et al 2010; Wigglesworth 1964). Maternal dietary restrictions also are widely utilized in rodents to induced IUGR.…”
Section: Animal Models Of Iugr With β-Cell Dysfunctionmentioning
confidence: 99%
“…In a further rat model of uterine artery ligation, IGF-1 treatment during the early postnatal period saw no effect on body or brain weight, which was associated with an increase in hepatic IGFBP-3 [ 80 ]. Little work has been undertaken in the non-human primate (NHP) model in the context of developmental programming.…”
Section: Animal Models Of Manipulation Of the Gh-igf Axismentioning
confidence: 99%
“…Several studies reported various reduced placental flow FGR models primarily using the complete ligation of the bilateral uterine arteries with silk threads [ 16 , 17 , 18 , 19 ]. However, it is suggested that in this ligation model, most of the fetal rats proximal to the ligation site will die, and fetal rats far from the ligation site will not experience FGR because of the blood flow from the bilateral ovarian arteries.…”
Section: Introductionmentioning
confidence: 99%